Maximising the nutritional and sensory quality of Lupin bread made using Western Australian bakers flour - Villarino, Casiana Blanca Jucar (Curtin University, 2014)
Australian sweet lupin (ASL) addition to bread has potential to increase its nutritional quality. ASL variety significantly affected ASL-wheat bread quality, related to varietal differences in composition and flour particle size. Factorial analysis identified the most significant process parameters affecting ASL-wheat bread quality. Response surface methodology identified optimal levels of process and formulation parameters to deliver ASL-lupin bread with maximum ASL incorporation combined with acceptable physical quality and consumer acceptability.